2017
DOI: 10.3389/fpsyt.2017.00250
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Immune Alterations in Major Depression: The Role of Subtypes and Pathogenetic Characteristics

Abstract: Depression has been associated with peripheral inflammatory processes and alterations in cellular immunity. Growing evidence suggests that immunological alterations may neither be necessary nor sufficient to induce depression in general, but seem to be associated with specific features. Using baseline data from the Outcome of Psychological Interventions in Depression trial, this exploratory study examines associations between depression subtypes and pathogenetic characteristics (i.e., melancholic vs non-melanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…NLR was related to a later onset of depression. Thus, in line with the vascular depression hypothesis as one distinct etiopathological mechanism, a later onset of depression is associated with pathological pathways relevant for cardiovascular disease has been supported 28 . Although NLR was still higher in depressed patients than healthy controls, in our analysis we could not show a significant difference.…”
Section: Discussionmentioning
confidence: 74%
“…NLR was related to a later onset of depression. Thus, in line with the vascular depression hypothesis as one distinct etiopathological mechanism, a later onset of depression is associated with pathological pathways relevant for cardiovascular disease has been supported 28 . Although NLR was still higher in depressed patients than healthy controls, in our analysis we could not show a significant difference.…”
Section: Discussionmentioning
confidence: 74%
“…To date, a large number of studies have demonstrated that depression has been associated with positive regulation of interleukin-8 production and immune response (18, 50, 51). Euteneuer et al (52) revealed that patients with MDD exhibited higher neutrophil and monocyte counts and an increased neutrophil to lymphocyte ratio (NLR) than controls. They also found that lower anti-inflammatory activity was related to more severe somatic depressive symptoms.…”
Section: Mdd Major Depressive Disorder; Cns Central Nervous Systemmentioning
confidence: 99%
“…The dysregulation of the immune system as an aetiological factor, but also affecting the course of depression, is no longer questionable [32,33]. D'Acquisto [34] uses the term affective immunol- ogy.…”
Section: Emotional Immunity or Immune Emotionality? The Key To Undersmentioning
confidence: 99%